Pengaruh Kemoterapi Terhadap Asupan Makan Dan Status Gizi Penderita Kanker Nasofaring Di Ruang Rawat Inap RSUD Dr. Moewardi Di Surakarta - NINGRUM, Dyah Ayu Retno; , Tuti Rahmawati, S.Gz.,M.Si; , Ahmad Farudin, SKM, M.Si (2015)
Introduction: Chemotherapy is one method of cancer treatment methods that using the drugs which can destroy the cancer cells or stop the development of cancer cells. The effects of chemotherapy include nausea and vomiting that may affect the food intake and indirectly may affect the nutritional status of nasopharynx cancer patient. Objective: To determine the effect of chemotherapy toward food intake and nutrition status of nasopharynx cancer patients in Dr. Moewardi Hospital Surakarta. Method of Research: This research uses observational research design with cross sectional research design. The number of research sample is 20 samples. The data of food intake for food from the hospital uses Comstock method and food from outside the hospital with a 24-hour recall method for 3 consecutive days. The determination of nutrition status patients uses BMI (Body Mass Index) of measurements of body weight in kilograms divided by height in meters squared. The statistical test that is used Fisher's Exact Test. Results: The result of statistical test shows that there is no chemotherapy effect in energy intake with p = 0.150 and protein intake with p = 0.150. There is a chemotherapy effect in fat intake with p = 0.016 and carbohydrate intake with p = 0.016. Based on the statistical test for the effect of chemotherapy on nutritional status showed no effect of chemotherapy on nutritional status, with p = 0.242. Conclusion: There is no chemotherapy effect in energy intake, protein intake and nutritional status. There is chemotherapy effect in fat and carbohydrate intake.